Small Quasi Primary Submodules - J. Abdul-Alkalik, Adwia (Al-Nahrain Journal of Science, 2025)
In this research, a new concept (small quasi-primary submodules) has been presented, which is a generalization of a previously studied concept (quasi-primary submodules) and a comprehensive study of it in terms of features and properties. We have also given some examples and observations about it. Its relationship with previously studied concepts was studied, and the equivalence, under certain conditions, between these concepts and the new concept was demonstrated.